2020
DOI: 10.1108/md-10-2019-1500
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial passion, orientation and behavior: the moderating role of linear and nonlinear thinking styles

Abstract: PurposeThe purpose of this paper is to unpack the underlying mechanisms of entrepreneurs' passion, orientation and behavior by investigating the role of rational and nonrational cognitive elements. Building on dual process theory and sociointuitionism, a conceptual model is proposed in order to explore the relationship between entrepreneurial passion, entrepreneurial orientation (EO) and strategic entrepreneurship behavior (SEB). Specifically, entrepreneurs' linear thinking styles (System 2) and nonlinear thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 95 publications
(185 reference statements)
8
28
0
6
Order By: Relevance
“…As an assumption, we realize that our H1 and H2 are supported. These results are in line with hypotheses proposed in the literature, where it is theorized that cognitive styles have differences in information processing and decision-making and thus could explain IEO [29,75]. However, during our research, the literature found that relates the two dimensions were scarce and, in a study conducted by Cools and Broeck [75], it was found that cognitive styles were not shown to be of significant contribution in explaining EO when compared to other individual traits (ambiguity tolerance, self-efficacy, proactive personality, locus of control, and need for achievement).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As an assumption, we realize that our H1 and H2 are supported. These results are in line with hypotheses proposed in the literature, where it is theorized that cognitive styles have differences in information processing and decision-making and thus could explain IEO [29,75]. However, during our research, the literature found that relates the two dimensions were scarce and, in a study conducted by Cools and Broeck [75], it was found that cognitive styles were not shown to be of significant contribution in explaining EO when compared to other individual traits (ambiguity tolerance, self-efficacy, proactive personality, locus of control, and need for achievement).…”
Section: Discussionsupporting
confidence: 92%
“…The study of its antecedents has been scarce [75], however, it is perceived that IEO also has a cognitive approach which tries to understand the aspects of cognition that are important in the entrepreneurial process, so it makes sense to associate cognitive differences with the way strategy is seen by entrepreneurs [29,75]. Within the few studies found, a recent work by Zollo et al [29] shows the conduct of a study in small and medium European organizations where they concluded that cognitive styles are mediators in the causal relationship between entrepreneurial passion, IEO and strategic entrepreneurship behaviour.…”
Section: Individual Entrepreneurial Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this dual process theory of cognition may have different denominations, each denomination is grounded in the notion that the human mind depends on two types of mental processing to perform routine tasks (Grayot, 2019). From this foundation, Zollo et al (2021) relate the dual-process theory of cognition to linear and thinking.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…On the one hand, nonlinear thinking acknowledges the role of emotions, impulsiveness and passion in upholding the entrepreneurial orientation, thus inspiring affectively consistent strategic and management decisions (Larsen, 2020). On the other hand, rational and deliberative thinking fosters the entrepreneurs' ability to handle the challenges that arise from the growth of the entrepreneurial venture (Zollo et al, 2020). They mould entrepreneurial decisions via analytical reasoning and calculative logics, drawing on organizational capabilities and information processing skills developed by entrepreneurs over time (Morales Burgos et al, 2020).…”
Section: Unfolding the Dance Of Entrepreneurial Decision Makingmentioning
confidence: 99%